Gmelina (Gmelina arborea Roxb.) Growth in Some Agroforestry Pattern in Village Sekarwangi, Sub-district Malangbong, District Garut - Nurheni Wijayanto; Ida Rosita (Jurnal Silvikultur Tropika, 2012)
Agroforestry is land used system which combines woody plants (trees, shrubs, rattan) with woody plants or may not with the grass (pasture), sometimes there is a component of the cattle and other animals that formed the ecological interactions between woody plants and other components. The selection of inappropriate agroforestry pattern will affect the growth of staple crops with a high competition to get nutrient elements, air, and light from the sun. This research aims to analyze the influence of agroforestry patterns of gmelina growth and analyze the relationship of land management system on the gmelina growth. This research was done in  Village Sekarwangi, Malangbong, Garut in December 2011 to February 2012. This study used  RAL  analysis with one factorial, agroforestry pattern. There are three patterns of agroforestry  chosen as the treatment. Parameters was observed is  gmelina  dimensions form of  total high, diameter, high free branches, and diameter of  crops. The result showed that agroforestry pattern one exert most good against growth gmelina. It obtained based on the fingerprint variety test and duncan test. Pattern agroforestry one give highest average on each parameter. Besides that, system land management of agroforestry one also exert best to the gmelina growth.